Revitalizing the student's learning motivation using interactive Angklung media during Pandemic - Listyaningsih, Selvi; Riyanto, Yatim; Yani, Muhammad Turhan (International Journal for Educational and Vocational Studies, 2023)
The study aims to regenerate students' learning motivation by focusing on the use of culture-based learning media owned by the Indonesian nation. This research is a type of qualitative descriptive research, the problem will be described in words by minimizing the use of numbers, the process of collecting and analyzing data is carried out in a narrative manner. Data collection techniques in research at SD Negeri Mojowarno I Jombang were carried out using observation, interviews and documentation studies. In this study, several stages were applied, namely the pre-field stage, the field work stage, data analysis and data report generation. The results of this study indicate that it is concluded that the interactive angklung media that is applied in Social Sciences (IPS) material is an effective learning media to foster student learning motivation, especially during the Covid-19 pandemic, through this interactive angklung learning media the enthusiasm of students in learning begins to grow. and rekindled again.